Learning Strategies at SD Muhammadiyah 1 Waru During Pandemic Covid 19 - Ririn Dwi Jayanti (International Consortium of Education and Culture Research Studies, 2021)
This study aims to describe online learning during the Covid19 pandemic as a learning strategy and learning outcomes for Muhammadiyah 1 Waru Elementary School students. The implementation of quarantine and self-isolation that is recommended by the government of course will not only affect the work of the community, but also have an impact on the education system which must continue to run as well at SD Muhammadiyah 1 Waru implementing health protocols which are usually activities which are usually carried out in classrooms on The school environment has now changed to learning at home.